2017
DOI: 10.1111/geb.12596
|View full text |Cite
|
Sign up to set email alerts
|

Fire and plant diversity at the global scale

Abstract: Aim Understanding the drivers of global diversity has challenged ecologists for decades. Drivers related to the environment, productivity and heterogeneity are considered primary factors, whereas disturbance has received less attention. Given that fire is a global factor that has been affecting many regions around the world over geological time scales, we hypothesize that the fire regime should explain a significant proportion of global coarse‐scale plant diversity. Location All terrestrial ecosystems, excludi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
98
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 87 publications
(139 reference statements)
3
98
1
5
Order By: Relevance
“…That the best regression model is related to fire number for both tMIC and tMAC is surprising given that the majority of recent studies suggest significant relationships between charcoal and burned area or fire intensity (Colombaroli & Gavin, ; Duffin et al, ; Higuera et al, ; Leys et al, , Appendix S13). Early calibration studies, where regional scales and/or long historical fire records were considered (MacDonald et al, ; Tinner et al, ) also identified fire number as a significant factor explaining charcoal abundance at regional scales, in accordance with more recent observations (Pausas & Ribeiro, ). Furthermore, this parameter is very sensitive to uncertainties in the amount of time contained within a sediment sample, possibly explaining why it was not significant in studies where only charcoal concentrations (and not influx) were calculated (Duffin et al, ; Whitlock & Millspaugh, ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…That the best regression model is related to fire number for both tMIC and tMAC is surprising given that the majority of recent studies suggest significant relationships between charcoal and burned area or fire intensity (Colombaroli & Gavin, ; Duffin et al, ; Higuera et al, ; Leys et al, , Appendix S13). Early calibration studies, where regional scales and/or long historical fire records were considered (MacDonald et al, ; Tinner et al, ) also identified fire number as a significant factor explaining charcoal abundance at regional scales, in accordance with more recent observations (Pausas & Ribeiro, ). Furthermore, this parameter is very sensitive to uncertainties in the amount of time contained within a sediment sample, possibly explaining why it was not significant in studies where only charcoal concentrations (and not influx) were calculated (Duffin et al, ; Whitlock & Millspaugh, ).…”
Section: Discussionsupporting
confidence: 65%
“…intensity) and area burned. Fire frequency has been found to be indicative of a region's fire-related land-use practices and population densities (Catry et al, 2010) but is also linked to regional fire-proneness and flammability (Pausas & Ribeiro, 2017). While fire intensity refers to the energy release of a fire, the area burned is related to fuel connectivity and is useful for calculating fire rotation periods (Bond & Keeley, 2005), as well as fire-related carbon emissions (van der Werf, Peters, van Leeuwen, & Giglio, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Fires not only modify plant and animal community compositions, but also the biotic interactions (García, Castellanos, & Pausas, ; Pausas & Parr, ), with consequences for ecosystem functioning and the services they provide. While the effect of wildfires on plant communities is well studied across many ecosystems around the world (Bradstock, Williams, & Gill, ; Keeley, Bond, Bradstock, Pausas, & Rundel, ; Pausas & Ribeiro, ), their effect on biotic interactions is still poorly known. An especially relevant interaction is pollination, as most flowering plants (85%), including most crops (75%), rely on animal pollinators for sexual reproduction (Klein et al, ; Ollerton, Winfree, & Tarrant, ).…”
Section: Introductionmentioning
confidence: 99%
“…A escala global la diversidad vegetal responde positivamente con la actividad del fuego, debido a que este retrasa la exclusión competitiva, y genera heterogeneidad de ambientes y nuevos nichos (Pausas & Ribeiro, 2017). Sin embargo, la respuesta al fuego a escala local puede variar entre biomas y ecosistemas (Pausas & Ribeiro, 2017).…”
Section: Discussionunclassified
“…Sin embargo, la respuesta al fuego a escala local puede variar entre biomas y ecosistemas (Pausas & Ribeiro, 2017). Nuestro trabajo muestra que en base a 23 años de registro de la frecuencia de fuego, la riqueza vegetal no responde de acuerdo con lo predicho por la hipótesis de disturbio intermedio (Connell, 1978;Huston, 1979), pues aquí observamos la menor riqueza de especies tanto en los sitios de baja como de alta frecuencia de fuego.…”
Section: Discussionunclassified